(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article presents the results of scientific research conducted in the field of library science, the results of a retrospective analysis of foreign and domestic research conducted in this field, the results of the analysis of dissertations on this topic It is known that dissertations traditionally serve as a certain "indicator" when determining the directions of scientific research and an information base for determining trends in the development of disciplines in the field under study. It is necessary to study the priority directions of the development of the Information and Library fields in developed foreign countries, as well as to determine our promising tasks and scientific priorities.